Correlation between Mother’s Nutritional Knowledge with Nutritional Status (Height for Age and BMI for Age) of Children - Komala, Ramadhana; Febriani, Wiwi; Ariska, Karin; Nurrahmawati, Erfha (Universitas Islam Negeri Raden Intan Lampung, 2023)
Malnutrition problems usually occur in early childhood. It is pretty concerning because early childhood is a group whose nutritional needs must be considered and are still growing. Lack of maternal nutritional knowledge is one of the causes of nutritional problems in children. This study analyzed the relationship between mothers' nutritional knowledge and children's nutritional status (TB/U and IMT/U) at Raudlatul Ulum, Ambarawa District, Pringsewu Regency. The research design was cross-sectional, with 31 subjects. The research subjects were mothers with children aged >60 months. The type of analysis used is Fisher's Test. The results of the study showed that the number of children with stunting nutritional status (TB/U) was seven people (22.6%), which became a public health problem (stunting prevalence >20%). The number of children with poor nutritional status (IMT/U) is one person (3.2%). Statistical test results showed that there was no significant relationship (p>0.05) between the mother's nutritional knowledge and the toddler's nutritional status (TB/A and IMT/U). Still, there was a significant relationship due to the difference in the proportion of> 20%. In conclusion, a mother's nutrition knowledge is essential in providing nutritious food and can support children's nutritional status.